Pengaruh Faktor Ekonomi Makro Terhadap Fluktuasi Harga Saham di Sektor Teknologi - Suhendra, David Xavier Timotius; Airawaty, Diana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Indonesia's technology industry has experienced substantial growth, though it remains relatively nascent compared to other well-established sectors. This growth has resulted in considerable stock price fluctuations for technology companies listed on the Indonesian Stock Exchange (IDX), especially amid shifts in macroeconomic conditions. The stock price decline from 2021 to 2023 underscores the importance of understanding the effects of factors. Previous studies have yielded mixed and inconclusive results regarding the impact of macroeconomic variables on stock prices across various industries, emphasizing the need for further exploration in the developing technology sector. This study investigates the impact of macroeconomic factors on the stock prices of technology firms on the IDX. Employing a quantitative approach with multiple linear regression, this study analyzed secondary data from 44 companies during the 2021-2023 period. Data were obtained using purposive sampling and examined through descriptive statistical methods, classical assumption testing, and regression analysis, using SPSS version 23. The results reveal that inflation and interest rates significantly influence stock prices, while exchange rates show no significant association.